2013
DOI: 10.1186/1744-8603-9-21
|View full text |Cite
|
Sign up to set email alerts
|

Screening for diabetes and hypertension in a rural low income setting in western Kenya utilizing home-based and community-based strategies

Abstract: BackgroundThe burdens of hypertension and diabetes are increasing in low- and middle-income countries (LMICs). It is important to identify patients with these conditions early in the disease process. The goal of this study, therefore, is to compare community- versus home-based screening for hypertension and diabetes in Kenya.MethodsThis was a feasibility study conducted by the Academic Model Providing Access to Healthcare (AMPATH) program in Webuye, a town in western Kenya. Home-based (door-to-door) screening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
84
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(89 citation statements)
references
References 21 publications
1
84
1
3
Order By: Relevance
“…Low numbers of individuals utilizing healthcare providers after community and home-based screening events was also observed in other sub-Saharan African settings [1518]. Some of the reasons for this low attendance include individual (e.g.…”
Section: Discussionmentioning
confidence: 82%
“…Low numbers of individuals utilizing healthcare providers after community and home-based screening events was also observed in other sub-Saharan African settings [1518]. Some of the reasons for this low attendance include individual (e.g.…”
Section: Discussionmentioning
confidence: 82%
“…However, while linkage to care is known to be a challenge, both in Kenya 9 and elsewhere in sub-Saharan Africa, [10][11][12] specific factors influencing linkage to hypertension care have not been identified in this population.…”
Section: Introductionmentioning
confidence: 94%
“…21−23 One study in Western Kenya reported a prevalence of 8% in a neighbouring rural population. 24 Dyslipidaemia is an abnormal lipid profile that is evidenced by any or all of the four (elevated levels of total plasma cholesterol, low-density lipoprotein cholesterol, triglycerides and reduced levels of high-density lipoprotein cholesterol). 25−29 Through atherosclerosis, dyslipidaemia is a well-documented risk factor for CVD.…”
Section: Introductionmentioning
confidence: 99%